Analisis Dampak Inflasi Terhadap Daya Beli Konsumen dalam Konteks Ekonomi - Helin Syafitri; Rozalinda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study analyzes the impact of inflation on consumer purchasing power in Indonesia, focusing on low-income communities and micro, small, and medium enterprises (MSMEs). Using a descriptive qualitative method, data were collected through in-depth interviews and field observations. The results show that inflation has a significant effect on daily consumption patterns and the quality of life, particularly in meeting basic needs. Moreover, the increase in essential goods prices has triggered social instability in several regions. This study also evaluates government policies in mitigating the impact of inflation and provides recommendations to protect the most vulnerable groups from rising prices. The findings suggest that although fiscal and monetary policies have short-term positive effects, more comprehensive measures are needed for the long term.